2018
DOI: 10.1161/circgen.117.001893
|View full text |Cite
|
Sign up to set email alerts
|

Ion Channel Dysfunctions in Dilated Cardiomyopathy in Limb-Girdle Muscular Dystrophy

Abstract: Background: Limb-Girdle muscular dystrophies (LGMD) are a heritable group of genetically determined disorders with a primary involvement of the pelvic or shoulder girdle musculature with partially cardiac manifestation, such as dilated cardiomyopathy (DCM) and life-threatening tachyarrhythmia. We report here that human induced pluripotent stem cell (hiPSC)–derived cardiomyocytes from a patient with LGMD2I and DCM associated with recurrent ventricular tachycardia displayed ion channel dysfunction an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 45 publications
1
34
0
Order By: Relevance
“…This animal model is not ideal, either, because the differences between animals and humans—as well as the differences between the drug‐induced SQTS and disease‐induced SQTS—may influence the results of drug testing. Our group has successfully used human‐induced pluripotent stem cell–derived cardiomyocytes (hiPSC‐CMs) to model some key features of different diseases, including SQTS1 . We have demonstrated that the hiPSC‐CMs from an SQTS1 patient (SQTS1 hiPSC‐CMs) are able to recapitulate the single‐cell phenotypic features of SQTS (APD‐shortening and arrhythmic calcium transients) and provide novel opportunities to further elucidate the disease mechanism and test drug effects …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This animal model is not ideal, either, because the differences between animals and humans—as well as the differences between the drug‐induced SQTS and disease‐induced SQTS—may influence the results of drug testing. Our group has successfully used human‐induced pluripotent stem cell–derived cardiomyocytes (hiPSC‐CMs) to model some key features of different diseases, including SQTS1 . We have demonstrated that the hiPSC‐CMs from an SQTS1 patient (SQTS1 hiPSC‐CMs) are able to recapitulate the single‐cell phenotypic features of SQTS (APD‐shortening and arrhythmic calcium transients) and provide novel opportunities to further elucidate the disease mechanism and test drug effects …”
mentioning
confidence: 99%
“…Our group has successfully used human-induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs) to model some key features of different diseases, including SQTS1. [22][23][24][25][26][27][28] We have demonstrated that the hiPSC-CMs from an SQTS1 patient (SQTS1 hiPSC-CMs) are able to recapitulate the single-cell phenotypic features of SQTS (APDshortening and arrhythmic calcium transients) and provide novel opportunities to further elucidate the disease mechanism and test drug effects. 27 Therefore, we designed the current study to examine the APDprolonging and antiarrhythmic effects of some drugs using our well-defined and characterized model of SQTS1.…”
mentioning
confidence: 99%
“…11:e001893. El-Battrawy et al (2018) [ 52 ] DM1 Disease modeling Cell Reprogram. 15:237–48 Xia (2013) [ 53 ] DM1 Therapeutic genome editing Stem Cells.…”
Section: Human Ipsc As Models For Disease Mechanism Studies and Drug mentioning
confidence: 99%
“…The detailed molecular or electrophysiological mechanism is not defined because of the difficulties of accessing live human cardiac cells and animal models failed to demonstrate cardiomyopathy [ 83 ]. A recent study using human iPSC model shed light on the pathogenesis [ 52 ]. The author found that human iPSC-derived cardiomyocytes from a patient with LGMD2I (patient also has dilated cardiomyopathy associated with recurrent ventricular tachycardia) exhibited sodium, calcium, and K+ channel dysfunction, leading to reduced amplitude and upstroke velocity of action potentials as well as diminished Ca 2+ release.…”
Section: Human Ipsc As Models For Disease Mechanism Studies and Drug mentioning
confidence: 99%
“…In addition, substantial interline variability in cardiac differentiation capacity exists, emphasizing the need for reliable controls. Nevertheless, hiPSCs have been successfully used to model several cardiovascular diseases ( Brandao et al., 2017 ; El-Battrawy et al., 2018 ; Goedel et al., 2017 ; Moretti et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%